2020
DOI: 10.18203/2394-6040.ijcmph20204374
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of speech language and hearing impairment in school going children of rural area: a longitudinal study

Abstract: Background: This study aimed on identifying children with hearing, speech and language disorders in rural population that are not identified, diagnosed or rehabilitated yet. The study also focused on collecting a large data with increased study duration to give an appropriate representation of the findings in a rural population.Methods: Subjective tests were used to screen for hearing, speech and language disorders.Results: On performing audiological and speech language tests, 130 children were found to have h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
1
7
2
Order By: Relevance
“…The present study results revealed a total of 75 (3.25%) children with hearing and otological problems which is similar to the study by Savithri et al 14 which reported 3.4% of prevalence rate for hearing disorders among school children and also a study by Varsha et al 16 who reported presence of hearing and otological problems in 85 children among 1453 school children. Further, among the 75 children with hearing and otological problems, 53 (2.30%) children were having otological problems such as impacted curemen, perforation, ear pain, etc which is lesser in contrast to the findings of previous studies by Chadha et al, 18 who reported a prevalence rate of 17.92% among school children in northern India and also a study by Parvez et al 20 who reported a prevalence rate of 17.9% among school children of Aligarh district.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The present study results revealed a total of 75 (3.25%) children with hearing and otological problems which is similar to the study by Savithri et al 14 which reported 3.4% of prevalence rate for hearing disorders among school children and also a study by Varsha et al 16 who reported presence of hearing and otological problems in 85 children among 1453 school children. Further, among the 75 children with hearing and otological problems, 53 (2.30%) children were having otological problems such as impacted curemen, perforation, ear pain, etc which is lesser in contrast to the findings of previous studies by Chadha et al, 18 who reported a prevalence rate of 17.92% among school children in northern India and also a study by Parvez et al 20 who reported a prevalence rate of 17.9% among school children of Aligarh district.…”
Section: Discussionsupporting
confidence: 91%
“…20 Otological impairments are more frequent seasonal (rainy & winter) weather changes, may be leading to common middle ear pathologies in the school children, 34 especially among children from rural areas due to poor hygiene, lack of awareness and socioeconomic issues. 17,18,19,35 A total of 24 children (1.04%) out of total 2304 school children were identified to have speech and language disorders which is lesser in contrast to the prevalence rate of 10.6% reported by Savithri et al 14 and 3.09% by Varsha et al 16 The present study revealed stuttering and speech sound disorders are more prevalent among school children compared to other speech and language disorders. The majority of developmental language disorders in school children were due to the presence of impairments in sensory, functional and intellectual abilities with poorer access to the rehabilitative services, poor modeling and reinforcement by teachers & parents 14 and certain sensory loss can also affect academic the performances of children.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations